Kluczowa rola rodziny i rówieśników w edukacji językowej dzieci/uczniów o zróżnicowanych potrzebach = The key role of family and peers in the language education of children/students with diverse needs - Janiszewska-Nieścioruk, Zdzisława; Nieścioruk, Julia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the current globalized and commercialized reality, knowledge of foreign languages is an essential communication tool that facilitates both establishing relationships and cooperating with others. At the same time, knowledge of English is considered a priority because of its wide use in international business, science, the Internet, social media and many other areas of life.
Keywords: nauczanie języka obcego; dzieci/uczniowie o specjalnych potrzebach; rola rodziców i rówieśników w edukacji językowej dziecka; foreign language education; children/students with special needs; the role of parents and peers in a child?s language education